PENERAPAN ASAS POLLUTER PAY PRINCIPLE DAN STRICT LIABILITY TERHADAP PELAKU PEMBAKARAN HUTAN - Malvin Edi Darma; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2018)
The environment is a very important part of human life. Therefore, the destruction of the environment, especially the destruction of forests, must be overcome. One method of doing this is through the enforcement of the environment law. Increasingly, the awareness in the enforcement of environmental law is also growing, as evidenced by the enforcement of environmental law through strict liability and polluter pay principle approach. The principle of Strict liability and polluter pay principle in the enforcement of environmental law in Indonesia is regulated in the provisions of Articles 88 and 87 of Law No. 32 of 2009 on Environmental Protection and Management. However, the problem remains as the application of the principle of strict liability and polluter pay principle has not reached its full effectivity in the enforcement of environmental law in Indonesia. Based on these two principles, the perpetrators of environmental destruction, namely the forest burners, are responsible for losses caused by their deeds. Therefore, this research will discuss the application of strict liability principle and polluter pay principle in enforcing environmental law against forest burning actors.